Unveiling Fashion Business, Culture, and Identity in the Most Glamorous Industry - Godart, F. (INSEAD Business Press, 2012)
Proposing a comprehensive account of the global fashion industry this book aims to present fashion as a social and cultural fact. Drawing on six principles from the industry, Godart guides the reader through the economic, social and political arena of the world's most glamorous industry.